2011
DOI: 10.1089/jir.2010.0051
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin's Effect on Intestinal Inflammation and Tumorigenesis in the ApcMin/+Mouse

Abstract: Curcumin's benefits on tumorigenesis are thought to be mediated by its antiinflammatory activity; however, these effects have not been well characterized in a mouse model of colon cancer. We examined the effects of curcumin on intestinal inflammation in the Apc Min/þ mouse. Apc Min/þ mice were given a placebo or curcumin (2%) diet from 4 to 18 weeks of age (n ¼ 10/group). C57BL/6 mice were used as a wild-type control (n ¼ 10/ group). Intestines were analyzed for polyp burden (sections 1, 4, and 5) and for mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 28 publications
4
28
1
2
Order By: Relevance
“…However, wide variability exists between reported studies. The number of colonic tumors in this study was high but is comparable to that observed by others (38)(39)(40). The reasons for this variability remain in large part unexplained, but differences in housing conditions, diet composition, and microbiota may be have induced changes in the intestinal microenvironmental factors implicated in colon tumor formation (8,41,42) Carnitine plays a key role in the metabolism of fatty acids (17,22).…”
Section: Discussionsupporting
confidence: 91%
“…However, wide variability exists between reported studies. The number of colonic tumors in this study was high but is comparable to that observed by others (38)(39)(40). The reasons for this variability remain in large part unexplained, but differences in housing conditions, diet composition, and microbiota may be have induced changes in the intestinal microenvironmental factors implicated in colon tumor formation (8,41,42) Carnitine plays a key role in the metabolism of fatty acids (17,22).…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have indicated that anticancer properties of CUR are related to enzymes such as COX-2, AMPK, MMPs, NADPH and LOX; transcription factors such as NF-κB, AP-1, β-catenin and STAT-3 and protein kinases and growth factors such as MAPK, AKT, JAK, VEGF, ERK, PKA and Bcl-2 ( Figure 8). 13,[91][92][93][94] More details are discussed later.…”
Section: Application Of Cur Liposomes On Cancermentioning
confidence: 99%
“…Quantification of gene expression for macrophage phenotype [IL-12 and IL-23 (M1 macrophage phenotype), IL-13, CD206, TGF-␤, and CCL17 (M2 macrophage phenotype)], T cell markers (CD8 and Foxp3), and inflammatory mediators [IL-1␤, IL-6, TNF-␣, SOCS1 (suppressor of cytokine signaling 1)] were performed as previously described (28,29). Briefly, mucosal tissue and polyps were homogenized under liquid nitrogen with a Polytron, and total RNA was extracted by using TRIzol reagent (Invitrogen).…”
Section: Animals Apcmentioning
confidence: 99%